Study of wear properties of Al7075-SiC-Gr composites using Taguchi and ANOVA methods. (19th December 2022) - Manjunath, T.S.; ,; Kumar, M.V. Praveen; Rudresh, M.
This research work aims to study the wear properties of Al7075 grade aluminium based MMCs reinforced with SiC and Gr particles. Powder metallurgy process was followed to fabricate the composites with Al7075 particle sizes of 24 μm and 50 μm, SiC with varying weight amounts of 6, 12 and 18% and graphite (Gr) with constant weight of 4%. The composite samples were tested for wear loss and coefficient of friction using pin-on-disc wear test apparatus under dry conditions with varying sliding speed, distance and applied load. The experiments were designed using Taguchi L18 orthogonal array. The findings from S/N ratio and ANOVA approaches revealed that the most significant parameters influencing the wear loss were SiC content and applied load, while for the friction coefficient were applied load and sliding distance. Composite properties were improved by the amalgamation of smaller matrix particles (24 μm) and a higher reinforcement content (18 wt%).